Analisis kepuasan kualitas pelayanan MTs Al-Muttaqin Pekanbaru sebagai pembentuk citra sekolah dan customer loyalty - Detry Jufri; Sri Kartikowati; Sumarno (Universitas Kanjuruhan Malang, 2023)
The research aims to determine customer satisfaction based on the quality of school services that can shape the school's image and customer loyalty. The research approach used mixed method research with a sequential mixed methods type with a sequential explanatory strategy. This research used interviews and questionnaires as research instruments. Total of 151 were chosen by using probability sampling with stratified random sampling. The data had collected then analyzed with univariate analysis, servqual analysis, and importance-performance analysis. The results of the research conducted, there are differences between expectations and reality for all dimensions of the quality of school services that are measured. Furthermore, the results of the interviews conducted showed that the dimensions of physical evidence are things that need to be improved, but in terms of teacher quality, it is already good. Those results indicate that customer satisfaction has not achieved yet, when referring to the theory of customer satisfaction. Schools are expected to be able to make improvements to the quality of service to students so that they can become a bridge to establish good communication with parents and be able to create positive perceived values ​​for schools.